WEBVTT
00:00:00.520 --> 00:00:07.160
In this lesson, weβll learn how to write a quadratic equation given the roots of another quadratic equation.
00:00:07.720 --> 00:00:13.080
Letβs begin by recalling the relationship between the roots of a quadratic and the coefficients of its terms.
00:00:13.920 --> 00:00:36.080
For a quadratic equation of the form ππ₯ squared plus ππ₯ plus π equals zero, by the quadratic formula, its solutions, and as its roots are π one and π two, are π one equals negative π plus the square root of π squared minus four ππ over two π.
00:00:36.600 --> 00:00:44.440
And π two is equal to negative π minus the square root of π squared minus four ππ over two π.
00:00:45.280 --> 00:00:50.400
Weβre now going to find the sum and product of these general roots.
00:00:51.040 --> 00:00:53.760
The sum is π one plus π two.
00:00:54.360 --> 00:00:57.320
The expression for the sum is shown.
00:00:57.880 --> 00:01:07.480
But of course, we can split the first fraction up into negative π over two π plus the square root of π squared minus four ππ over two π.
00:01:08.040 --> 00:01:18.160
And then, we can split the second fraction into negative π over two π minus the square root of π squared minus four ππ over two π.
00:01:18.840 --> 00:01:25.800
And now, we see that the second term and the fourth term sum to make zero; essentially, they cancel.
00:01:26.280 --> 00:01:35.360
And so, we have negative π over two π plus negative π over two π, which is negative two π over two π.
00:01:35.880 --> 00:01:43.960
Finally, we can cancel by dividing both the numerator and denominator of our fraction by two, leaving us with negative π over π.
00:01:44.720 --> 00:01:47.640
So, the sum of our roots is negative π over π.
00:01:48.200 --> 00:01:52.280
In other words, itβs the negative of the coefficient of π₯ over the coefficient of π₯ squared.
00:01:52.760 --> 00:01:55.840
Weβre now going to repeat this process to find the product.
00:01:56.440 --> 00:02:01.680
Product means multiply, so weβre doing π one times π two.
00:02:02.400 --> 00:02:06.400
Once again, we split the first fraction up, and then we split the second fraction up.
00:02:06.960 --> 00:02:15.280
And weβre now going to distribute by multiplying the first terms, the outer terms, the inner terms, and the last terms.
00:02:16.080 --> 00:02:20.320
Multiplying the first terms gives us π squared over four π squared.
00:02:20.720 --> 00:02:33.320
Then, multiplying the outer and inner terms gives us the positive and negative versions of π times the square root of π squared minus four ππ all over four π squared.
00:02:33.760 --> 00:02:35.760
Now, of course, the sum of these is zero.
00:02:36.320 --> 00:02:38.600
So, these terms are actually going to cancel.
00:02:39.600 --> 00:02:47.560
Then, when we multiply the last terms, we get negative π squared minus four ππ all over four π squared.
00:02:48.040 --> 00:02:58.840
Weβre now going to split this second fraction up, remembering, of course, that since weβre going to be subtracting negative four ππ over four π squared, thatβs the same as adding it.
00:02:59.280 --> 00:03:06.400
And so we should see now that π squared over four π squared minus π squared over four π squared is zero.
00:03:07.120 --> 00:03:16.720
Similarly, we can divide through by an π and by the four in this final fraction, and that leaves us simply with π over π.
00:03:17.280 --> 00:03:25.040
And we can therefore say that the product of the two roots of a quadratic equation is the constant term divided by the coefficient of π₯ squared.
00:03:25.680 --> 00:03:49.880
Now whilst this might not seem like a hugely useful result, if we go back to our original equation ππ₯ squared plus ππ₯ plus π equals zero and divide through by π β weβre allowed to do this, of course, cause π is not going to be equal to zero β we see that our quadratic equation becomes π₯ squared plus π over ππ₯ plus π over π equals zero.
00:03:50.680 --> 00:03:55.560
And now, we should see that these link to our earlier results.
00:03:56.040 --> 00:04:02.600
Negative π over π is the same as the negative coefficient of π₯, and π over π is the constant term.
00:04:03.240 --> 00:04:16.960
And so, weβre now able to say that a quadratic equation whose leading coefficient is one can be written as π₯ squared minus the sum of roots times π₯ plus the product of the roots equals zero.
00:04:17.760 --> 00:04:21.800
So, letβs have a look at an example of how we might apply these results.
00:04:22.480 --> 00:04:37.240
Given that πΏ plus three and π plus three are the roots of the equation π₯ squared plus eight π₯ plus 12 equals zero, find, in its simplest form, the quadratic equation whose roots are πΏ and π.
00:04:38.120 --> 00:04:44.480
Letβs begin by recalling the relationship between a quadratic equation whose leading coefficient is one and its roots.
00:04:44.800 --> 00:04:52.520
We can write the equation in the form π₯ squared minus that sum of the roots times π₯ plus the product of the roots equals zero.
00:04:53.080 --> 00:05:03.000
And so, if we consider our equation π₯ squared plus eight π₯ plus 12 equals zero, the sum of the roots must be negative eight.
00:05:03.480 --> 00:05:14.040
Now, the reason itβs negative eight and not positive eight is because in the general form, the coefficient of π₯ is the negative sum of the roots, and in our example, the coefficient is positive.
00:05:14.800 --> 00:05:20.360
We can also say that the product, which is the constant term, must be equal to 12.
00:05:21.000 --> 00:05:25.520
And often weβll look to replace the roots with the roots given in the question.
00:05:26.160 --> 00:05:30.120
So here the roots are πΏ plus three and π plus three.
00:05:30.560 --> 00:05:36.680
But in fact, weβre able to calculate two numbers which have a sum of negative eight and a product of 12.
00:05:37.360 --> 00:05:45.760
Two numbers which satisfy this result are negative six and negative two, and this is because a negative times a negative is a positive.
00:05:46.200 --> 00:05:49.360
So, negative six times negative two is positive 12.
00:05:49.840 --> 00:05:53.880
But also, negative six plus negative two is negative eight.
00:05:54.480 --> 00:06:02.040
And so, defining our roots to be π one and π two, we see that theyβre equal to negative six and negative two.
00:06:02.640 --> 00:06:07.640
But of course, we were told that the roots of this equation are πΏ plus three and π plus three.
00:06:08.160 --> 00:06:13.640
So we can form two equations, one in πΏ and one in π.
00:06:14.280 --> 00:06:21.520
The first equation is πΏ plus three equals negative six, and the second is π plus three equals negative two.
00:06:21.960 --> 00:06:28.640
Weβll solve both of these equations for their respective variable by subtracting three from both sides.
00:06:29.400 --> 00:06:32.760
Negative six minus three is negative nine.
00:06:33.160 --> 00:06:35.680
So πΏ must be equal to negative nine.
00:06:36.200 --> 00:06:38.800
Similarly, π is equal to negative five.
00:06:39.320 --> 00:06:44.080
And so this is really useful because we now know the roots to our new equation.
00:06:44.640 --> 00:06:49.520
We can form this equation by finding the sum of these roots and the product.
00:06:49.960 --> 00:06:55.400
The sum is negative nine plus negative five, which is negative 14.
00:06:55.760 --> 00:07:00.840
And the product is negative nine times negative five, which is 45.
00:07:01.760 --> 00:07:11.040
And so now that we know that the sum of our roots is negative 14 and the product is 45, we can substitute these back into the general form.
00:07:11.600 --> 00:07:24.200
That gives us π₯ squared minus negative 14 times π₯ plus 45 equals zero, and this simplifies to π₯ squared plus 14π₯ plus 45 equals zero.
00:07:25.080 --> 00:07:27.720
Weβre now going to look at a similar example.
00:07:28.160 --> 00:07:37.080
But this time, weβre not going to be able to easily work out the roots of our original equation, and so weβre going to use algebra to find the new equation.
00:07:37.760 --> 00:07:50.360
Given that πΏ and π are the roots of the equation π₯ squared minus two π₯ plus five equals zero, find, in its simplest form, the quadratic equation whose roots are πΏ squared and π squared.
00:07:50.920 --> 00:07:57.080
Letβs begin by recalling the relationship between a quadratic equation whose leading coefficient is one and its roots.
00:07:57.600 --> 00:08:04.880
We can represent it as π₯ squared minus the sum of the roots times π₯ plus the product of the roots equals zero.
00:08:05.400 --> 00:08:22.080
And so, this is essentially saying that if we have a quadratic equation equal to zero and the leading coefficient is one, in other words, the coefficient of π₯ squared is one, the negative coefficient of π₯ will tell us the sum of the roots and the constant term will tell us its product.
00:08:22.600 --> 00:08:28.360
So we take the equation π₯ squared minus two π₯ plus five equals zero.
00:08:28.960 --> 00:08:30.720
The coefficient of π₯ is negative two.
00:08:31.040 --> 00:08:37.880
And so the sum must be the negative of negative two, so the sum of the roots must be positive two.
00:08:38.600 --> 00:08:40.280
Then the constant term is five.
00:08:40.800 --> 00:08:44.240
So the product of the roots must be five.
00:08:44.840 --> 00:08:49.760
So can we find two numbers that have a sum of two and a product of five?
00:08:50.440 --> 00:08:52.840
Well, no, not easily.
00:08:53.240 --> 00:08:55.880
Weβre not going to get nice integer solutions.
00:08:56.440 --> 00:09:00.600
And so instead, weβre going to form equations using πΏ and π.
00:09:01.440 --> 00:09:10.480
Since the sum of our roots is two and πΏ and π are the roots, we can say πΏ plus π must be equal to two.
00:09:11.000 --> 00:09:14.400
And then we can say that πΏ times π is equal to five.
00:09:15.080 --> 00:09:18.480
The roots of our new equation are πΏ squared and π squared.
00:09:18.800 --> 00:09:34.240
And so, since their sum will be πΏ squared plus π squared, we need to manipulate our equations to find an expression for πΏ squared plus π squared and another expression for their product, πΏ squared π squared.
00:09:34.880 --> 00:09:37.480
Letβs label our equations as one and two.
00:09:38.200 --> 00:09:41.360
Weβre going to take the entirety of equation one and, weβre going to square it.
00:09:41.360 --> 00:09:43.760
In other words, we square both sides.
00:09:44.320 --> 00:09:48.000
So on the right-hand side, we get two squared, which is, of course, equal to four.
00:09:48.520 --> 00:09:55.240
Then, on the left-hand side, we get πΏ plus π squared, which we can consider to be πΏ plus π times πΏ plus π.
00:09:56.000 --> 00:10:02.640
And if we distribute these parentheses, we get πΏ squared plus two πΏπ plus π squared equals four.
00:10:03.160 --> 00:10:10.600
And then, if we subtract two πΏπ from both sides, we get the expression for the sum of the roots πΏ squared and π squared.
00:10:10.960 --> 00:10:12.960
Itβs four minus two πΏπ.
00:10:13.800 --> 00:10:21.000
But of course, we have an expression for πΏπ; equation two tells us that πΏπ is equal to five.
00:10:21.360 --> 00:10:31.200
And so, πΏ squared plus π squared becomes four minus two times five, which is four minus 10 or simply negative six.
00:10:31.640 --> 00:10:38.000
So, we found the sum of the roots of our new equation and, therefore, the negative coefficient of π₯.
00:10:38.720 --> 00:10:43.440
Weβre now going to repeat this process for equation two; weβre going to square both sides.
00:10:44.040 --> 00:10:48.400
That is, πΏπ squared equals five squared.
00:10:49.000 --> 00:10:51.600
But, of course, five squared is 25.
00:10:51.960 --> 00:10:54.520
And we can distribute to the power of two across both terms.
00:10:54.920 --> 00:10:59.320
And we get πΏ squared π squared equals 25.
00:11:00.000 --> 00:11:07.320
We, therefore, find that the sum of our new roots is negative six and the product is 25.
00:11:07.960 --> 00:11:10.520
Letβs substitute these back into the general form.
00:11:11.040 --> 00:11:17.400
When we do, we get π₯ squared minus negative six π₯ plus 25 equals zero.
00:11:17.800 --> 00:11:28.200
And so, the quadratic equation whose roots are πΏ squared and π squared is π₯ squared plus six π₯ plus 25 equals zero.
00:11:29.200 --> 00:11:38.520
In our next example, weβll look at using the relationship between the coefficients of a quadratic and its roots to help us find the value of an expression.
00:11:39.400 --> 00:11:49.480
If πΏ and π are the roots of the equation π₯ squared plus 20π₯ plus 15 equals zero, what is the value of one over π plus one over πΏ?
00:11:50.480 --> 00:11:55.680
We begin by reminding ourselves what the relationship between the coefficient of a quadratic equation is and its roots.
00:11:56.400 --> 00:12:09.520
For a quadratic equation whose leading coefficient is one, in other words, the coefficient of π₯ squared is one, the negative coefficient of π₯ tells us the sum of the roots and the constant term tells us the product.
00:12:09.920 --> 00:12:16.440
And this is really useful because the coefficient of π₯ here is 20 and the constant is 15.
00:12:17.040 --> 00:12:19.920
And so, the sum of our roots must be negative 20.
00:12:20.560 --> 00:12:23.760
Remember, we said that itβs the negative coefficient of π₯.
00:12:24.360 --> 00:12:29.120
Then, the product, which is the constant term, must be 15.
00:12:29.880 --> 00:12:33.680
But of course, we were told that πΏ and π are the roots of our equation.
00:12:34.080 --> 00:12:42.520
So we can, in fact, say that πΏ plus π must be negative 20 and πΏ times π must be 15.
00:12:43.200 --> 00:12:44.640
So, how does this help?
00:12:45.680 --> 00:12:55.880
Weβre looking to find the value of one over π plus one over πΏ, and we canβt easily find two numbers that have a sum of negative 20 and a product of 15.
00:12:56.520 --> 00:12:59.320
So weβre going to need to manipulate our expressions.
00:12:59.840 --> 00:13:04.080
Letβs think of one over π plus one over πΏ.
00:13:04.920 --> 00:13:08.400
We know that to add two fractions, we need to create a common denominator.
00:13:08.800 --> 00:13:15.600
Now, the easiest way to do this when working with algebraic fractions is to multiply both parts of each fraction by the denominator of the other.
00:13:16.040 --> 00:13:22.800
So, weβre going to multiply the numerator and denominator of our first fraction by πΏ and of our second fraction by π.
00:13:23.440 --> 00:13:27.640
That gives us πΏ over πΏπ plus π over πΏπ.
00:13:28.400 --> 00:13:36.240
And now since the denominators are the same, we simply add the numerators, and that gives us πΏ plus π over πΏπ.
00:13:37.000 --> 00:13:45.840
And this is really useful because we know that the numerator πΏ plus π is equal to negative 20, and then the denominator πΏπ is 15.
00:13:46.320 --> 00:13:56.280
And this means, in turn, that one over π plus one over πΏ is equal to negative 20 over 15, which simplifies to negative four-thirds.
00:13:56.560 --> 00:14:05.080
And so, if πΏ and π are the roots of our equation, then one over π plus one over πΏ must be equal to negative four-thirds.
00:14:05.760 --> 00:14:09.960
Weβre now going to extend this idea into forming quadratic equations.
00:14:10.760 --> 00:14:25.040
Given that πΏ and π are the roots of the equation three π₯ squared plus 16π₯ minus one equals zero, find, in its simplest form, the quadratic equation whose roots are πΏ over two and π over two.
00:14:25.880 --> 00:14:29.280
Letβs begin by recalling the relationship between the quadratic equation and its roots.
00:14:29.600 --> 00:14:39.560
For a quadratic equation whose leading coefficient is one, we can say that the coefficient of π₯ is the negative sum of the roots of the equation, whereas the constant is the product of its roots.
00:14:40.200 --> 00:14:44.720
Now, comparing this to our equation, we see we do have a bit of a problem.
00:14:45.200 --> 00:14:48.480
The leading coefficient, the coefficient of π₯ squared, is three.
00:14:48.920 --> 00:14:51.600
And so, weβre going to divide every single term by three.
00:14:52.000 --> 00:14:55.080
Three π₯ squared divided by three is π₯ squared.
00:14:55.440 --> 00:15:03.040
16π₯ divided by three is 16π₯ over three or 16 over three π₯.
00:15:03.520 --> 00:15:06.160
And then, our constant term becomes negative one-third.
00:15:06.720 --> 00:15:12.560
And so, comparing this to the general form, we know that the sum of the roots of our equation is the negative coefficient of π₯.
00:15:13.240 --> 00:15:16.440
So, itβs negative 16 over three.
00:15:17.000 --> 00:15:19.160
Then, the product is negative one-third.
00:15:19.600 --> 00:15:29.680
But weβre also told that πΏ and π are the roots of our equation, so we can replace these with πΏ plus π as the sum and πΏ times π as the product.
00:15:30.440 --> 00:15:35.400
Weβre looking to find the quadratic equation whose roots are πΏ over two and π over two.
00:15:36.040 --> 00:15:43.040
And so, what weβre going to do is find an expression for the sum of these roots; thatβs πΏ over two plus π over two.
00:15:43.640 --> 00:15:51.240
Similarly, weβre going to find the product of these roots; thatβs πΏ over two times π over two which is πΏπ over four.
00:15:51.920 --> 00:15:54.920
So, how can we link the equations we have?
00:15:55.360 --> 00:15:58.040
Well, letβs call this first equation one.
00:15:58.520 --> 00:16:01.760
We have πΏ plus π as being equal to negative 16 over three.
00:16:02.360 --> 00:16:10.680
If we divide the entire expression by two, that is πΏ plus π over two, we actually know thatβs equal to πΏ over two plus π over two.
00:16:11.280 --> 00:16:19.280
And so, this means we can find the value of πΏ over two plus π over two by dividing the value for πΏ plus π by two.
00:16:19.840 --> 00:16:26.440
Thatβs negative 16 over three divided by two, which is negative eight over three.
00:16:27.040 --> 00:16:29.720
And we can repeat this process with our second equation.
00:16:30.240 --> 00:16:32.840
This time, of course, we want πΏπ divided by four.
00:16:33.320 --> 00:16:38.440
So thatβs going to be negative one-third divided by four, which is negative one twelfth.
00:16:39.240 --> 00:16:45.720
And now that we have the sum of our roots and the product, we can substitute these back into our earlier equation.
00:16:46.240 --> 00:17:00.920
When we do, we find that the quadratic equation whose roots are πΏ over two and π over two is π₯ squared minus negative eight over three π₯ plus negative one twelfth equals zero.
00:17:01.640 --> 00:17:04.800
Letβs simplify a little by dealing with our signs.
00:17:05.400 --> 00:17:10.440
In other words, negative negative eight-thirds is just eight-thirds.
00:17:10.960 --> 00:17:15.560
And adding negative one twelfth is the same as subtracting one twelfth.
00:17:16.320 --> 00:17:19.240
Our final step is to create integer coefficients.
00:17:19.600 --> 00:17:23.120
And to do so, weβre going to multiply through by 12.
00:17:23.680 --> 00:17:26.880
π₯ squared times 12 is 12π₯ squared.
00:17:27.360 --> 00:17:31.600
Then, if we multiply eight-thirds by 12, we cancel a three.
00:17:32.120 --> 00:17:36.600
And we end up working out eight times four, which is 32.
00:17:37.120 --> 00:17:40.760
Negative one twelfth times 12 is negative one.
00:17:41.400 --> 00:17:45.000
And, of course, zero times 12 is zero.
00:17:45.000 --> 00:17:52.640
And so, the quadratic equation is 12π₯ squared plus 32π₯ minus one equals zero.
00:17:53.720 --> 00:17:57.400
Letβs now recap the key points from this lesson.
00:17:57.960 --> 00:18:08.000
In this video, we learned that for an equation of the form ππ₯ squared plus ππ₯ plus π equals zero, the sum of the roots is negative π over π.
00:18:08.560 --> 00:18:12.440
Itβs the negative coefficient of π₯ divided by the coefficient of π₯ squared.
00:18:12.880 --> 00:18:15.120
And the product is π over π.
00:18:15.560 --> 00:18:19.000
Itβs the constant term divided by the coefficient of π₯ squared.
00:18:19.640 --> 00:18:27.760
We can use this information to express the relationship between the roots of a quadratic whose leading coefficient is one and the coefficient of its terms.
00:18:28.320 --> 00:18:37.320
When the equation is written in this form, the negative coefficient of π₯ tells us the sum of the roots, whereas the constant term tells us the product.